Post-traumatic stress disorder among the staff of a mental health hospital: Prevalence and risk factors - Anthony A. Olashore; Oluyemi O. Akanni; Keneilwe Molebatsi; John A. Ogunjumo (South African Journal of Psychiatry, 2018)
Background: Mental health service providers are frequently exposed to stress and violence in the line of duty. There is a dearth of data concerning the psychological sequelae of the frequent exposure to stress and violence, especially among those who work in resource-limited countries such as Botswana.